PARENTS PERSPECTIVES ON HOMESCHOOLING MANAGEMENT MODEL IN BANGKOK, THAILAND - Ren, Qian; Phongsatha, Thanawan (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2021)
The objectives of this study were to 1) investigate the reasons for choosing homeschooling of the Thai families in Bangkok; 2) explore the different activities or forms of Thai homeschooling families choose to engage their children in Bangkok; and 3) identify the social interaction skills of the homeschooled children from the Thai families in Bangkok; 4) study the academic outcome of the homeschooled children from the Thai families in Bangkok. The research was conducted with 44 Thai homeschooling families in Bangkok. The sample were families who chose to homeschool the children. The sampling technique was non-probability sampling method with purposive sampling plan to recruit samples to participate in the study. The open-ended questions were applied as the research instrument. The content validity with the S-CVI procedure was applied to measure the validity of the question items. The rating of 1.00, which was suitable for evaluating the content validity of the questions was revealed to ensure that the questions were valid. All 44 families had completed the questions. Among them, there were additional in-depth interviews with 10 families. The results from the qualitative data showed that the homeschooling families were generally satisfied with their children’s performance and learning outcome. Feedback from both the children and the parents suggest that homeschooling is more flexible and easier to adapt to different needs and situations of children while comparing to formal school system.